2011
DOI: 10.1101/gad.17027411
|View full text |Cite
|
Sign up to set email alerts
|

miR-17∼92 cooperates with RB pathway mutations to promote retinoblastoma

Abstract: The miR-17~92 cluster is a potent microRNA-encoding oncogene. Here, we show that miR-17~92 synergizes with loss of Rb family members to promote retinoblastoma. We observed miR-17~92 genomic amplifications in murine retinoblastoma and high expression of miR-17~92 in human retinoblastoma. While miR-17~92 was dispensable for mouse retinal development, miR-17~92 overexpression, together with deletion of Rb and p107, led to rapid emergence of retinoblastoma with frequent metastasis to the brain. miR-17~92 oncogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(194 citation statements)
references
References 44 publications
10
180
3
1
Order By: Relevance
“…In the present study, we demonstrated a significant correlation between the miR-17-92 cluster level and the proliferation, invasion and migration of osteosarcoma cells: the expression of miR-17-92 cluster was higher in cells with higher proliferation, invasion and migration potential. The positive association of miR-17-92 cluster with cell proliferation, invasion and migration suggests that miR-17-92 cluster may be categorized as a "metastasis promotor gene" in osteosarcoma, which was in line with previous reports [22,33,34].…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we demonstrated a significant correlation between the miR-17-92 cluster level and the proliferation, invasion and migration of osteosarcoma cells: the expression of miR-17-92 cluster was higher in cells with higher proliferation, invasion and migration potential. The positive association of miR-17-92 cluster with cell proliferation, invasion and migration suggests that miR-17-92 cluster may be categorized as a "metastasis promotor gene" in osteosarcoma, which was in line with previous reports [22,33,34].…”
Section: Discussionsupporting
confidence: 80%
“…ECs lacking the 17∼92 cluster grew more slowly, as measured by BrdU incorporation, consistent with the known function of the cluster in promoting cell growth via repression of E2F or PTEN (Fig. 3A) (2,4,9,(29)(30)(31). ECs lacking the miR-17∼92 cluster demonstrated augmented adhesion to either gelatin or fibronectin, complementing data showing that overexpression of the cluster reduces adhesion (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Conversely, inhibiting miR-17∼92 may provide clinical benefit in PKD by increasing the expression of PKD1, PKD2, and HNF-1β. miR-17∼92 is known to regulate other signaling pathways, such as mTOR and TGF-β pathways, which are also implicated in the pathogenesis of cyst growth (28,(40)(41)(42). Bioinformatics algorithms predict that members of the miR-17∼92 cluster target thousands of mRNAs for posttranscriptional silencing.…”
Section: Discussionmentioning
confidence: 99%